Toward a better integration of requirements and model‐based specifications. Issue 6 (5th October 2020) - Lebeaupin, Benoît; Rauzy, Antoine
Abstract: As of today, most specifications of technical systems still rely on requirements written in natural language. However, this approach is known to be problem‐prone, due to the inherent ambiguity of natural languages. On the other hand, fully formal or model‐based approaches seem to be out of reach in many practical cases, especially in early design phases of systems. In this article, we study how to combine in a pragmatic way natural language requirements with models. We propose to keep both formats and to link pieces of text in requirements with elements of models. In other words, corpuses of requirements are managed as hypertexts with links to models. For this approach to be fully efficient, the text of requirements is not free, but relies on controlled natural language techniques leading to a partial structuring of the text. We show that this makes it possible to design (semi)automatic verifications on requirements and models, which would be impossible with unconstrained natural language. We illustrate here our approach on a small illustrative example and we report results obtained on a full size industrial application.